Value at Risk Disclosures: The Case of Canada Revisited - Alkhub, Hala (2011)
This paper is based on the empirical analysis that has been conducted by (Pérignon, Deng and Wang, 2007), to test whether the Royal bank of Canada (RBC) and the Bank of Montreal (BMO) are overstating their Value at Risk (VaR). This study is based on non-anonymous data of the daily VaR and P&L for both banks within the period starting from the year 2001 till the year 2010. The paper exhibits results contradicting those of (Pérignon, Deng and Wang, 2007) , it shows that RBC and BMO do not overstate their VaR; in other words the banks are accurate in disclosing their VaR measure according to the data derived from the analyses performed. The data used in this paper is based on the graphs extracted from the banks’ annual reports using the R software for computing statistics to transfer the graphs into time series data. After extracting the data conditional and unconditional coverage tests were performed to test the accuracy of disclosing daily VaR and profit and loss data. Two benchmarks have been developed; the Historical Simulation and the GARCH model to compare the commercial banks' VaR with the forecasted VaR depending on the benchmarks.